The challenge of self-directed and self-regulated learning in vocational education : a theoretical analysis and synthesis of requirements - Jossberger, Helen [Verfasser]; Brand-Gruwel, Saskia [Verfasser]; Boshuizen, Henny [Verfasser]; Wiel, Margje van de [Verfasser] (My University, 2010)
"Workplace simulations (WPS), authentic learning environments at school, are increasingly used in vocational education. This article provides a theoretical analysis and synthesis of requirements considering learner skills, characteristics of the learning environment and the role of the teacher that influence good functioning in WPS and foster students' learning. WPS appeal to students' self-directed learning (SDL) and self-regulated learning (SRL) skills, as students are required to work and learn independently in these settings. To achieve individual learning, the environments should be adaptive to the learners' needs. Furthermore, the teachers should support learners to become competent in the domain but also guide them to become self-directed learners. To do so the interaction between the student, the teacher and the environment is of importance. The proposed model depicts the different elements and their relations." (Autorenreferat, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; L 2.1 Lernformen; S 1.3.3 Vollzeitschulische Berufsausbildung; I 2.2.1 Westeuropa; Lerntheorie; Selbstgesteuertes Lernen; Lernen am Arbeitsplatz; Kompetenzorientierung; Simulation; Praxisbezug; Lernarrangement; Lehrerrolle; Lehrer-Schüler-Beziehung; Schulische Berufsausbildung; Niederlande